Hubungan Faktor-Faktor Penyebab Kecemasan Dengan Tingkat Kecemasan Suami Menghadapi Istri Yang Bersalin Spontan Di Klinik Sehati Medan Tahun 2023 - Hasanah, Dwi Ris; Fitri, Sari Rahma (Universitas Sari Mulia, 2023)
Latar Belakang: Suami merasa cemas sewaktu mendampingi istri yang bersalin yang dipengaruhi oleh beberapa faktor yang dihubungkan dengan tingkat kecemasan.Tujuan: untuk mengetahui hubungan faktor-faktor kecemasan dengan tingkat kecemasan suami Menghadapi istri yang melahirkan secara spontan.Metode: penelitian ini menggunakan desain penelitian analitik dengan penedekatan cross sectional. Pengambilan sampel dengan menggunakan accidentalsampling. penelitian ini dilakukan di Klinik Sehati Medan.Hasil: mayoritas responden umur 31-35 tahun sebanyak 25 orang (48,1%), mayoritas pendidikan SMA 32 orang (61,5%), mayoritas responden berpenghasilan Rp. 1000.000,00-Rp. 2000.000,00 sebanyak 29 orang (55,8%). pada faktor keselamatan istri dan janin mayoritas ada pengaruh 40 orang (76,1%), faktor harapan jenis kelamin mayoritas berpengaruh 27 orang (51,9%), pada faktor tanggung jawab finansial tidak ada pengaruh 28 orang (53,8%) dan pada faktor anak lahir cacat ada pengaruh 31 orang (59,6%). Analisis data digunakan uji chi square.Kesimpulan: ada hubungan faktor keselamatan istri dan janin dengan tingkat kecemasan (p=0,04), ada hubungan faktor harapan jenis kelamin dengan tingkat kecemasan (p= 0,025), tidak ada hubungan faktor tanggung jawab finansial dengan tingkat kecemasan (p= 0,254), ada hubungan faktor anak lahir cacat dengan tingkat kecemasan (p=0,004). Dari hasil penelitian ini diketahui ada 3 faktor yang berhubungan dengan tingkat kecemasan suami Relationship between Factors Causing Anxiety and Husband's Anxiety Level Facing Wife in Spontaneous Delivery At Sehati Clinic Medan in 2023 Background: Husbands feel anxious when accompanying their wives in labor which is influenced by several factors associated with anxiety levels.Objective: to determine the relationship between anxiety factors and the level of anxiety of husbands Facing wives who give birth spontaneously.Methods: This study used an analytic research design with a cross sectional approach. Sampling using accidentalsampling. this research was conducted at the Sehati Clinic Medan.Results: the majority of respondents aged 31-35 years as many as 25 people (48.1%), the majority of high school education 32 people (61.5%), the majority of respondents earn Rp. 1000,000.00-Rp. 2000,000.00 as many as 29 people (55.8%). on the safety factor of the wife and fetus the majority there is an influence of 40 people (76.1%), the factor of gender expectations the majority influences 27 people (51.9%), on the factor of financial responsibility there is no influence 28 people (53.8%) and on the factor of birth defects there is an influence 31 people (59.6%). Data analysis used chi square test.Conclusion: there is a relationship between the safety factor of wife and fetus with anxiety level (p=0.04), there is a relationship between gender expectation factor with anxiety level (p=0.025), there is no relationship between financial responsibility factor with anxiety level (p=0.254), there is a relationship between birth defect factor with anxiety level (p=0.004). From the results of this study, it is known that there are 3 factors associated with the husband's anxiety level.